Experimental study of torsional strength of RC beams constructed with HPFRC composite mortar. (30th August 2015) - Kim, Jinsup; Kwon, Minho; Seo, Hyunsu; Lim, Jeonghee
Highlights: Torsional performance of RC beam with HPFRC composite mortar was evaluated. HPFRC composite mortar has high compressive and split tensile strength than plain concrete. Torsional performances of RC beam specimens were compared experimentally. HPFRC composite mortar enhanced the torsional performance of RC beam. Abstract: The torsional performance of reinforced concrete (RC) beam members covered with high-performance fiber-reinforced cementitious (HPFRC) composite mortar was evaluated through pure torsion tests. The HPFRC composite mortar has higher compressive strength and higher split tensile strength than plain concrete. Four beam specimens were constructed for the pure torsion test. Two types of section, and different materials, were used to produce the RC beam specimens. Various types of torsional performance (i.e., first-cracking torque, ultimate torque, and twist angles) were compared experimentally to evaluate the performance of the RC beam specimens. The torque and twist angle at first visible cracking, of the HPFRC composite mortar specimens were greater than those of the others. Therefore, the use of HPFRC composite mortar appears a useful method to enhance the torsional performance of RC-beam members. Moreover, a simple design equation to determine ultimate torque was proposed and tested, for predicting the torsional strength of RC beams with covers of HPFRC composite mortar. The proposed equation performed well.